1999
DOI: 10.4267/pollution-atmospherique.3386
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation du cadmium par quelques espèces végétales cultivées aux environs d'une usine d'engrais phosphatés à Sfax (Tunisie)

Abstract: Accumulation du cadmium par quelques espèces végétales cultivées aux environs d'une usine d'engrais phosphatés à Sfax (Tunisie) Accumulation of cadmium by some cultivated vegetable species around a factory producing phosphate fertilizers in Sfax (Tunisia) Imed MEZGHANI , Makki BOU KHRIS , Mohamed CHAIEB* RÉSUMÉ La pollution des écosystèmes terrest res par du cadmium d'origine industriell e (usine d'engr ais phosphatés) se traduit par des tach es nécrotiques au nivea u des feuilles et par une accumulation impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Based on the limits of contaminants in food (GB 2762-2005), the median value of fluoride content in vegetables was higher than the limit value (1 mg kg −1 ) by 129.00%, and 53.85% of vegetable samples exceeded this limit. This finding is similar to the studies reported by Mezghani et al [36] where large quantities of fluoride was accumulated by vegetation growing in vicinity of the factory. In the soil-vegetables system, vegetables efficiently absorb free fluoride ions, leading to the accumulation of fluoride, thus making vegetables a significant contributor to human exposure to fluoride [27].…”
Section: Fluoride Content In Vegetablessupporting
confidence: 92%
“…Based on the limits of contaminants in food (GB 2762-2005), the median value of fluoride content in vegetables was higher than the limit value (1 mg kg −1 ) by 129.00%, and 53.85% of vegetable samples exceeded this limit. This finding is similar to the studies reported by Mezghani et al [36] where large quantities of fluoride was accumulated by vegetation growing in vicinity of the factory. In the soil-vegetables system, vegetables efficiently absorb free fluoride ions, leading to the accumulation of fluoride, thus making vegetables a significant contributor to human exposure to fluoride [27].…”
Section: Fluoride Content In Vegetablessupporting
confidence: 92%
“…Several studies have used olive leaves as a bionidicator of air pollution (Sait et al, 2013;Mezghanni et al, 2000;Elloumi et al, 2003;Eliwa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%